2008
DOI: 10.1021/ol800480d
|View full text |Cite
|
Sign up to set email alerts
|

General, Robust, and Stereocomplementary Preparation of β-Ketoester Enol Tosylates as Cross-Coupling Partners Utilizing TsCl−N-Methylimidazole Agents

Abstract: We have developed a general, robust, and cost-effective method for the (E)- or (Z)-stereocomplementary enol tosylation of beta-ketoesters using TsCl- N-methylimidazole (NMI)-Et3N or LiOH. TsCl coupled with NMI formed a highly reactive N-sulfonylammonium intermediate. Stereocongested secondary alcohols were smoothly sulfonylated using Ts(Ms)Cl-NMI-Et3N. beta-Ketoesters underwent (E)-selective tosylation using TsCl-NMI-Et3N and (Z)-selective tosylation using TsCl-NMI-LiOH (total of 23 examples; 60%-99% yield). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…This observed reaction required Pd(OAc) 2 as a catalyst because a control experiment in the absence of catalyst produced no (Z)-3a (entry 12). The present reaction became less efficient with other oxidants such as KHSO 5 and Cu(OAc) 2 (entries [13][14][15]. However, reaction with p-benzoquinone as an oxidant produced an 84% yield (entry 16).…”
Section: Paper Syn Thesismentioning
confidence: 80%
See 4 more Smart Citations
“…This observed reaction required Pd(OAc) 2 as a catalyst because a control experiment in the absence of catalyst produced no (Z)-3a (entry 12). The present reaction became less efficient with other oxidants such as KHSO 5 and Cu(OAc) 2 (entries [13][14][15]. However, reaction with p-benzoquinone as an oxidant produced an 84% yield (entry 16).…”
Section: Paper Syn Thesismentioning
confidence: 80%
“…Finally, we found that other nucleophiles, ethanol, 2,4-dimethylbenzoic acid, and 4-methylbenzenesulfonamide, did not work under the standard conditions (entries 27-29). In short, the examples with electron-withdrawing functionality on sulfonic acids gave lower yields, such as 2,4-dinitrophenyl substitution (entry 13), and that with electron-donating moiety gave better yields, such as ethyl substitution (entry 21).…”
Section: Syn Thesismentioning
confidence: 99%
See 3 more Smart Citations